2011
DOI: 10.1111/j.1540-5915.2011.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative FMEA Method for Simple and Accurate Ranking of Failure Modes

Abstract: Failure modes and effects analysis (FMEA) is a methodology for prioritizing actions to mitigate the effects of failures in products and processes. Although originally used by product designers, FMEA is currently more widely used in industry in Six Sigma quality improvement efforts. Two prominent criticisms of the traditional application of FMEA are that the risk priority number (RPN) used to rank failure modes is an invalid measure according to measurement theory, and that the RPN does not weight the three dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…It is a straight forward step-by-step technique almost universally accepted as a method for systematically determining the ways in which failure can occur and also the effects (from minor to catastrophic) that each such failure can have on overall functionality The objective of FMECA is to anticipate failures and prevent them from occurring A good FMECA will: identify known and potential failure modes, identify cause and effect of each failure mode and provide for problem follow-up and corrective action, and prioritises the identified failure modes according to the RPN Bradley and Guerrero (2011) have acknowledged the wide use of FMECA in both product design and industry. However, they have identified two prominent criticisms of its traditional application viz.…”
Section: Failure Modes Effects and Criticality Analysismentioning
confidence: 99%
“…It is a straight forward step-by-step technique almost universally accepted as a method for systematically determining the ways in which failure can occur and also the effects (from minor to catastrophic) that each such failure can have on overall functionality The objective of FMECA is to anticipate failures and prevent them from occurring A good FMECA will: identify known and potential failure modes, identify cause and effect of each failure mode and provide for problem follow-up and corrective action, and prioritises the identified failure modes according to the RPN Bradley and Guerrero (2011) have acknowledged the wide use of FMECA in both product design and industry. However, they have identified two prominent criticisms of its traditional application viz.…”
Section: Failure Modes Effects and Criticality Analysismentioning
confidence: 99%
“…Wang et al [55] reported an FMEA method by using the house of reliability-based rough VIKOR approach. Other studies regarding prioritization of FMs can be found in [5], [12], [13], [18], [23], and [31].…”
Section: Prioritization Of Fms In Fmeamentioning
confidence: 99%
“…R ELIABILITY engineering addresses the estimation, prevention, and management of high levels of "lifetime" engineering uncertainty and risks of failure, which has received wide attention in various areas [16], [65]. Failure mode and effects analysis (FMEA) is a highly structured, and systematic reliability-management instrument, which is very useful for evaluating and eliminating potential failure modes (FMs) of products, processes, systems, and services [5], [39], [52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation exposes projects to a number of diverse and interdependent risks, which implies that identifying and analyzing their causes and effects is an important aspect. For instance, Failure Modes and Effects Analysis (FMEA) consists in a qualitative analysis of dysfunction modes and their effects [14]. Initially developed for product-related risks, it has been expanded to process-related and project-related risks, where the focus changes, but the principle is the same, consisting in identifying direct causes and effects of a potential failure.…”
Section: Introductionmentioning
confidence: 99%